Drugs and Academic Performance among Health Sciences Students at Two Latin American Universities (2017)
Introduction: Drug use among the young population of developing countries has increased in the last decades; educational and health institutions are concerned about this trend, as it can alter learning and memory, and particularly affects university students.Purpose: To describe and compare the relationship between drug use and academic performance among Health Sciences students at two Latin American universities.Method: Non-probability convenience sampling was used and the Drug Use among University Students Questionnaire (CODEU) was applied online. Data analysis was carried out based on descriptive statistics, and the point biserial correlation coefficient and Kruskal-Wallis non-parametric test were applied, considering the grade average obtained during the last period studied.Results: At the Universidad Veracruzana it was found that the use of alcohol, marijuana, cocaine and inhalable drugs decreases academic performance, while at the Universidad de Boyacá only the use of tranquilizers affected academic performance.Conclusions: It is important to continue conducting similar studies in order to obtain more accurate results and to clarify the relationship between drug use and academic performance. Therefore, it is recommended that variables related to the consequences of drug use be incorporated into indicators such as attendance, homework, and grades.